DETERMINAN NILAI PERUSAHAAN PADA PERUSAHAAN SUB-SEKTOR TRANSPORTASI DI BURSA EFEK INDONESIA - Maulida Magfhira, (2020)
This study aims to determine and analyze the determinants of firm value in transportation sub-sector companies in Indonesia Stock Exchange. The dependent variable in this study is firm value, while the independent variables in this study are firm size (Size), debt policy (DER), and profitability (ROE). The population in this study is the transportation sub-sector companies listed on the Indonesia Stock Exchange amounting to 43 companies. The sample selection in this study used a purposive sampling method and the final sample used is 24 firms in the transportation sub-sector with research period 2015-2019. The type of data used is secondary data and data analysis techniques used are descriptive statistics and panel data regression analysis using Microsoft Excel 2007 and Eviews 10 program. Based on the test result using a significant level of 0.05 and the final results indicate that the firm size (Size) has no significant effect on firm value (PBV), debt policy (DER) has a positive effect significant on firm value (PBV), and profitability (ROE) has no significant effect on firm value (PBV).